Missionary Journalism in the Early Republican Period: Folklor Postası - Harmanci, Meric (ISTANBUL UNIV, 2024)
Folklore journals have important value both in the past and currently in terms of allowing one to follow the course of folklore history research, the view and studies of the intellectuals of the period on folklore, and the information and findings obtained in research. The first folklore journal in T & uuml;rkiye was the Halk Bilgisi Mecmuas & imath; [The Folklore Periodical], which started its publication life in 1928. This journal was followed by Halk Bilgisi Haberleri [Folklore News], the first issue of which was published in 1929, and Folklor Dergisi [Folklore Journal], which started publication in 1943. However, Halk Bilgisi Mecmuas & imath; and Folklor Dergisi only published one issue each. Publishing 19 issues between 1944-1946, Folklor Postas & imath; [Folklore Post] was the second folklore magazine to be published regularly. This study aims to reveal the understanding of folklore and the course of folklore studies in the first period of the Republic by focusing on the articles and authors published in Folklor Postas & imath;, , one of the oldest Turkish folklore journals and an important area for Turkish folklore research. The analysis attempts to present a portrait of the Republic based on all 19 issues of Folklor Postas & imath; magazine. For this purpose, the analysis follows all traces in the magazine, from cover words and articles to visuals and researchers serving folklore. Folklor Dergisi is a treasure that provides a rich data source in terms of its content pertaining to Turkish culture, sociology, literature, history, and folklore and is a proof of the support Republican intellectuals gave to folklore through their works and writings in this current year when we celebrate the centennial of the Republic.
Keywords: Folklore; journalism; Folklor Postas & imath; mission; intellectual; Linguistics; Literature